Understanding the role of Staphylococcus aureus in atopic dermatitis: strain diversity, microevolution, and prophage influences - Wang, Zhongjie; Hülpüsch, Claudia; Traidl-Hoffmann, Claudia; Reiger, Matthias; Schloter, Michael (Frontiers in Medicine, 2024)
Atopic dermatitis (AD) is a prevalent inflammatory skin disorder characterized by chronic inflammation, skin barrier dysfunction, and microbial dysbiosis, with Staphylococcus aureus playing a significant role in its pathogenesis. This paper explores the strain diversity and microevolution of S. aureus within AD patients, emphasizing how specific strains adapt to the altered skin environment, exacerbating the condition. The review emphasizes the significance of variation in specific functional genes among S. aureus strains, which enhances their ability to adapt to different microenvironments and shapes their pathogenic potential. It also discusses how mobile genetic elements, particularly prophages, contribute to genetic diversity and drive the virulence and antibiotic resistance of S. aureus in AD, highlighting the clinical challenges posed by these strain-specific factors in managing the disease. The paper advocates for the integration of advanced genomic tools such as whole-genome sequencing and machine learning to develop targeted therapies. By focusing on the genetic adaptability of S. aureus and its impact on AD, this review underscores the need for strain-specific diagnostics and personalized treatment strategies to improve patient outcomes.